2003
DOI: 10.1073/pnas.1332441100
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction shapes babbling: Testing parallels between birdsong and speech

Abstract: Birdsong is considered a model of human speech development at behavioral and neural levels. Few direct tests of the proposed analogs exist, however. Here we test a mechanism of phonological development in human infants that is based on social shaping, a selective learning process first documented in songbirds. By manipulating mothers' reactions to their 8-month-old infants' vocalizations, we demonstrate that phonological features of babbling are sensitive to nonimitative social stimulation. Contingent, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
430
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(451 citation statements)
references
References 36 publications
(33 reference statements)
15
430
0
6
Order By: Relevance
“…One powerful intrinsic factor is developmental stage, often expressed as sensitive periods, as exemplified in the development of vision, language, and social behavior (Harlow et al, 1965;Katz, 1999;Newport et al, 2001). Recent studies have shown that environmental factors such as social interactions and environmental richness also modulate plasticity (Newport et al, 2001;Goldstein et al, 2003;Cancedda et al, 2004). Barn owls pass through a similar sensitive period during which experience exerts an exceptionally strong shaping influence on sound localization behavior (Knudsen and Knudsen, 1989b).…”
Section: Introductionmentioning
confidence: 99%
“…One powerful intrinsic factor is developmental stage, often expressed as sensitive periods, as exemplified in the development of vision, language, and social behavior (Harlow et al, 1965;Katz, 1999;Newport et al, 2001). Recent studies have shown that environmental factors such as social interactions and environmental richness also modulate plasticity (Newport et al, 2001;Goldstein et al, 2003;Cancedda et al, 2004). Barn owls pass through a similar sensitive period during which experience exerts an exceptionally strong shaping influence on sound localization behavior (Knudsen and Knudsen, 1989b).…”
Section: Introductionmentioning
confidence: 99%
“…Grey parrots (Psittacus erithacus), for example, have been shown to learn the proper use of referential labels only when provided interactive sessions with live tutors (e.g., Pepperberg, 1994Pepperberg, , 1998. Human infants have also been found to produce more sophisticated vocalizations when their mothers respond to their babbling in a contingent manner (Goldstein, King, & West, 2003). In contrast to such findings, filial imprinting has traditionally been viewed as a special type of learning that occurs largely independent of contingent interaction or overt reinforcement (e.g., Lorenz, 1935Lorenz, , 1937.…”
mentioning
confidence: 99%
“…Several recent studies have suggested that speakers do adjust their productions in response to listener feedback (Buz, Tanenhaus, & Jaeger, 2016;Goldstein, King, & West, 2003;Maniwa, Jongman, & Wade, 2009;Schertz, 2013;Seyfarth, Buz, & Jaeger, 2016;Warlaumont, Richards, Gilkerson, & Oller, 2014). Indeed, White (2013) has used listener feedback to train learners to produce alternations.…”
Section: Discussionmentioning
confidence: 99%